I. C. Christensens kirkepolitik og menighedsrådsloven af 1903 : En historisk undersøgelse af Den danske Folkekirkes moderne forfatning - Iversen, Gertrud (Kirkehistoriske Samlinger, 1992)
In this article the author sets out to analyse the genesis of one of the principal institutions in Danish religious life in this century, the parochial church councils. Focus is set on the first council-statute of 1903, concentrating on two issues in particular, firstly the intention of the statute, outlined by biographical analysis of its architect, the grand old man in Danish church politics, minister of Culture I. C. Christensen, and secondly the theological questions raised by introducing this lay institution. Here, for the first time, democracy entered the Church in Denmark on a more formal basis. By examining and describing the enclosed documents of the case together with contemporary sources relevant to the subject, the author outlines the various issues and interests at stake in a matter which was subject to political as well as theological dispute at almost every level. Since the constitution of 1849, the Church had been a national church, but without any formal order and regulation, and everybody - clergy as well as laity - could agree on the urgent need of a theological and practical solution to the situation. Opinions differed, however, when it came to solving the matter. I. C. Christensen’s solution was lay democracy in the form of church councils. Established by law and based on the local parish the object of this new institution was to be a first step towards an order for the church, thus - by means of modern democratic principles - fulfilling what the constitution of 1849 had outlined, but never carried through. It is one of the article’s main purposes to point out how virtually everybody was against it. Clergy as well as the two leading lay movements, the “left-wing” Grundtvigian one rooted in and centered on the rural population, and the “right-wing” and more pietistically orientated Indre Mission, engaged in mission among the urban population. Thus, what has become one of the principal institutions of Danish church life in this century was introduced by politicians in spite of the church itself! With the parochial church councils modern democracy entered the church. But, as history has shown, it did not solve the order problems of the 1849 National Church, nor was it given the intended central role in twentieth century church life. The clergy still has the leading role and secularisation has reduced public interest in ecclesiastical affairs to a minimum. In a concluding discussion the author argues that some of the most urgent questions in today’s protestant theology are raised in this matter: church-state relations, models of the church, and the role of the laity, and that the future of the Danish National Church depends on, the role the church council institution will be allowed to play in the coming decades.